2015
DOI: 10.4236/gep.2015.37002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metals Pollution in Soils and Vegetation around Selected Industries in Lagos State, Nigeria

Abstract: In this study, eleven soil samples and twenty-twoplants samples were collected in the vicinity of eleven industries and a thermal station was analyzed for zinc, copper, iron, lead and cadmium. Soil sample from Egbin thermal station had the highest concentration of Zn (141.06 mg/kg) and Cu (131.70 mg/kg). Soil from international textile had the highest level of Fe and the soil from Nichemtex had the highest concentration Pb and Cd was the highest in soil from Guinness (28.91 mg/kg, 59.80 mg/kg and 1.72 mg/kg re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 18 publications
(21 reference statements)
6
58
1
Order By: Relevance
“…Statistical analysis showed that Cd concentration in A. viridis and T. occidentalis in Sura market were significantly different (p<0.05) from other markets. Cadmium is a heavy metal with high toxicity and it is a non-essential element in foods and natural waters and it accumulates principally in the kidneys and liver (Divrikli et al, 2006;Adesuyi et al, 2015). Higher values have been previously reported for leafy vegetables cultivated along road sides (0.27 mg/kg) by Oluwole et al (2013 (Adesuyi et al, 2015).…”
Section: Nd-not Detectedmentioning
confidence: 89%
See 3 more Smart Citations
“…Statistical analysis showed that Cd concentration in A. viridis and T. occidentalis in Sura market were significantly different (p<0.05) from other markets. Cadmium is a heavy metal with high toxicity and it is a non-essential element in foods and natural waters and it accumulates principally in the kidneys and liver (Divrikli et al, 2006;Adesuyi et al, 2015). Higher values have been previously reported for leafy vegetables cultivated along road sides (0.27 mg/kg) by Oluwole et al (2013 (Adesuyi et al, 2015).…”
Section: Nd-not Detectedmentioning
confidence: 89%
“…Cadmium is a heavy metal with high toxicity and it is a non-essential element in foods and natural waters and it accumulates principally in the kidneys and liver (Divrikli et al, 2006;Adesuyi et al, 2015). Higher values have been previously reported for leafy vegetables cultivated along road sides (0.27 mg/kg) by Oluwole et al (2013 (Adesuyi et al, 2015). Cadmium accumulates especially in the kidneys leading to dysfunction of the kidney with increased secretion of e.g.…”
Section: Nd-not Detectedmentioning
confidence: 95%
See 2 more Smart Citations
“…Also, most heavy metals such as vanadium, lead, aluminium, nickel and iron, which are usually below detection in unused lubricating oil, have been reported to give high values (ppm) in used oil (Whisman et al, 1974;Adongbede and Sanni, 2014). These heavy metals may be retained in soils in the form of oxides, hydroxides, carbonates, exchangeable cations, and/or bound to organic matter in the soil (Yong et al, 1992;Adesuyi et al, 2015). Nevertheless, this is dependent on the local environmental conditions and on the kind of soil constituents present in the soilwater system.…”
Section: Introductionmentioning
confidence: 99%